Kinematical analysis on the last two steps and take-off technique of Chinese elite male long jumpers - Zhou, Q.; Xie, Z.-H.; Yao, T.-F.; Wu, W.-J.; Xu, J.-L.; Li, J. H. (Advances in Social Science, Education and Humanities Research, 2016)
Long jump is composed of the technical movements such as run-up, take-off, vacating and landing. The run-up and take-off techniques are the key factors to determine the performance in a long jump, especially the last several steps. In this paper, the last two steps and takeoff technique of the three Chinese elite male long jumpers, who entered the final competition in the World Athletics Championships in 2015, were analyzed using Dartfish video analysis system. The results showed that the jumping angle of the Chinese elite male long jumpers was at a reasonable range, but compare with the most elite athletes in the world, the last two steps and the takeoff technique of the Chinese elite male athletes were not perfect. The step distances of the last two steps of the most elite athletes in the world were "large-small", while these of the Chinese elite male long jumpers were "small-large", which resulted in a loss of horizontal speed; the takeoff sector angle of the Chinese elite male long jumpers was bigger than that of the most elite athletes in the world, which led to a loss of vacating height. Therefore, the last two steps and the takeoff technique of Chinese long jumpers are still needed to be improved.